Characterization of the complete mitochondrial genome sequence of medical spiny pipehorse Solegnathus spinosissimus and its phylogenetic analysis. Issue 1 (2nd January 2019) - Sun, Siya; Lai, Mengru; Huang, Zhen; Ge, Yuqing; Zhang, Guangji; Cheng, Rubin
Abstract: In the present study, we reported the complete mitochondrial genome sequence of the medical spiny pipehorse Solegnathus spinosissimus . It was 16, 530 bp in total length and contained 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and a control region. The overall base composition of S. spinosissimus was 26.94%, 30.21%, 17.54%, and 25.31% for A, C, G, and T, respectively. The length of 12S and 16S rRNA were 938 bp and 1667 bp, respectively. The phylogenetic analysis showed that S. spinosissimus was most closely related to S. hardwickii, providing additional evidence to support the previous morphological classification of genus Solegnathus . The molecular data of S. spinosissimus could contribute to the genetic diversity and species identification study in Syngnathidae family.